Pengembangan Bahan Ajar Materi Keragaman Flora Dan Fauna Di Indonesia Mata Pelajaran Ips Kelas VII MTs Negeri Surakarta 1 Tahun Ajaran 2014/2015 - Karomah, Karomah; , Drs. Suharjo, M.S (2015)
The bacground of this research is the provision of textbooks. He aim of this study was to determine the desired criteria of student textbooks and effectiveness of teaching materials developed books to improve student learning automes at MTs Surakarta 1, by developing teaching materials material diversity of flora and fauna in Indonesia. This research development model using Dick And Carrey , with pre test- post test the experimental class and control class. The results of product development of teaching materials of this book through the validation phase and expert lecturers through revisi stage . the results of student responses with an average value of 3.18 categorized as good and teachers with an average value of 3.57 considered very good. While the results of the research by using books teaching materials products. The averge value of the experimental class pretest posttest 65,21- be 88,6 and the average value of the control clss 59,7 pre test-post test became 74. From the above it can be concluded that there are differences between the experimental class after signifikasn treated products of teaching materials and books to know the diversity of flora and fauna in Indonesia kontrol without treatments products.